THE RELATIONSHIP OF VILLAGE HEAD LEADERSHIP AND CITIZENS' PARTICIPATION IN DEVELOPMENT IN TRANSMIGRANT VILLAGES - Kurniawan, Wahyu; Purba, Khairunsyah; Ummul Fithrriyyah, Mustiqowati (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2025)
Mahato Village is one of the transmigrant villages in Riau with a low level of citizen participation in development. This can be seen from the quiet presence of residents in the village planning meetings and their involvement in physical development. Another phenomenon that has yet to emerge is the intense loyalty of residents towards the leadership of the village head. This research aims to analyze the relationship between the leadership role of the village head in increasing community participation in development in transmigrant villages. This research was conducted using a qualitative approach. Data was collected through interviews with key informants, namely the Mahato village head, Mahato village secretary, Mahato village financial affairs head, BPD members, hamlet heads, and the community. Data collection was also carried out by observing and identifying attitudes and interactions between residents and village heads and observing various relevant village government documentation. The research results show that the Mahato Village Head's communication pattern has ineffective communication with residents in managing information related to programs and development; the village head's low level of innovation in identifying existing needs and problems has caused the group of residents' loyalty toward participation in the development process to be quiet. Desa mahato merupakan salah satu desa transmigran yang ada di Riau dengan tingkat partisipasi warga yang rendah dalam pembangunan. Hal ini dapat dilihat dari rendahnya kehadiran warga dalam musrenbangdes dan juga partisipasi dalam pembangunan fisik. Fenomena lain yang mengemuka adalah lemahnya loyalitas warga terhadap kepemimpinan kepala desa. Penelitian ini bertujuan untuk menganalisa relasi peran kepemimpinan kepala desa dalam meningkatkan partisipasi masyarakat dalam pembangungan di desa transmigran. Penelitian ini dilakukan dengan pendekatan kualitatif. Pengambilan data dilakukan melalui wawancara terhadap key informan yaitu kepala desa mahato, sekretaris desa mahato, kepala urusan keuangan desa mahato, anggota BPD, kepala dusun dan masyarakat. Pengambilan data juga dilakukan melalui observasi dengan cara mengamati dan mengidentifikasi sikap, interakasi antar warga dan kepala desa dan mengamati berbagai dokumentasi pemerintah desa yang relevan. Hasil penelitian menunjukkan bahwa pola komunikasi Kepala Desa Mahato memiliki komunikasi yang tidak efektif dengan warga dalam mengelola informasi terkait dengan program dan pembangunan, rendahnya inovasi kepala desa dalam mengidentifikasi kebutuhan dan permasalahan yang ada telah menyebabkan